Resolving the gene expression maps of human first-trimester chorionic villi with spatial transcriptome - Liu, Zhongzhen; Zhai, Man; Zhang, Qingqing; Yang, Tingyu; Wan, Zunmin; Li, Jianlin; Liu, Xiaofeng; Xu, Bo; Du, Libei; Chan, Rachel W. S.; Zhang, Li; Yeung, William S. B.; et al. (Frontiers in Cell and Developmental Biology, 2022)
The placenta is important for fetal development in mammals, and spatial transcriptomic profiling of placenta helps to resolve its structure and function. In this study, we described the landscape of spatial transcriptome of human placental villi obtained from two pregnant women at the first trimester using the modified Stereo-seq method applied for paraformaldehyde (PFA) fixation samples. The PFA fixation of human placenta villi was better than fresh villi embedded in optimum cutting temperature (OCT) compound, since it greatly improved tissue morphology and the specificity of RNA signals. The main cell types in chorionic villi such as syncytiotrophoblasts (SCT), villous cytotrophoblasts (VCT), fibroblasts (FB), and extravillous trophoblasts (EVT) were identified with the spatial transcriptome data, whereas the minor cell types of Hofbauer cells (HB) and endothelial cells (Endo) were spatially located by deconvolution of scRNA-seq data. We demonstrated that the Stereo-seq data of human villi could be used for sophisticated analyses such as spatial cell-communication and regulatory activity. We found that the SCT and VCT exhibited the most ligand-receptor pairs that could increase differentiation of the SCT, and that the spatial localization of specific regulons in different cell types was associated with the pathways related to hormones transport and secretion, regulation of mitotic cell cycle, and nutrient transport pathway in SCT. In EVT, regulatory pathways such as the epithelial to mesenchyme transition, epithelial development and differentiation, and extracellular matrix organization were identified. Finally, viral receptors and drug transporters were identified in villi according to the pathway analysis, which could help to explain the vertical transmission of several infectious diseases and drug metabolism efficacy. Our study provides a valuable resource for further investigation of the placenta development, physiology and pathology in a spatial context.